The Normalcy in Solomon Islands-Australia Asymmetric Relations Post-RAMSI - Faqih, Faqih (UI Scholars Hub, 2023)
Solomon Islands – China security deal has concerned Australia. Despite this, the relations between Solomon Islands and Australia have still been maintained through negotiated interaction. This article seeks to explain how Australia and Solomon Islands have sustained their normal relations even though Australia, as the larger power, has the means to exert its dominance over the Solomon Islands. The study employed a qualitative method by analyzing Solomon Islands and Australian leaders' statements collected from news media, official government websites, and official documents. Using Brantly Womack's conception of normalcy, the research found that the Solomon Islands still recognize the disparity of capabilities, while Australia still respects the Solomon Islands' sovereignty. The relationship has also been supported by frequent diplomatic exchanges and habituation through the shared experience during the RAMSI period. Lastly, the issue of contention has been successfully neutralized through persuasive rhetoric and issue depoliticization.